A gestão na Rede Sinodal de Educação - Becker, Tiago (2014)
This paper deals with school management in the Rede Sinodal de Educação [Sinodal Education Network] based on the analysis of texts and documents disclosed by the Network itself. The first part presents the concept of school management. A school has a unique responsibility toward society, to guarantee that the students learn. Therefore the management uses tools to promote the democratization of its processes, the participation of the people involved, the development and continuing learning process of its professionals as well as of the institution itself. The second part deals with the school management carried out in the Sinodal Education Network. The research revealed that the Lutheran Evangelical school seeks the continuous development of the people who work in it. There is a set of initiatives of the Network directed toward the development of leaderships who can work in the institution itself or in sister schools. Besides this, there is a clear relationship between the management and the Evangelical Lutheran principles which guide the pedagogical practice. Last, the research concluded that one of the major challenges of the management is to seek renewal so as to guarantee the survival of the institutions confronted with changes and new demands.